Monitoring of indoor ultrafine particulate matter at the fire rescue brigade workplaces. (October 2018) - Kellnerová, Eva; Kellner, Josef; Navrátil, Josef; Paulus, František
Abstract: The contribution deals with the issue of ultrafine particles in order of tens of nanometers in the air of Fire Rescue Brigade workplaces. Concerns about potential contact with air pollutants are arising even in situations, when these professionals are not deployed. The purpose of this work is to assess whether the presence of exposed persons in these workplaces is safe and does not in itself pose a risk of adverse health effects. Testing took place in two fire-fighting rooms. In the observed areas, mean particle counts were found at 1.02×10 4 and 2.51×10 4 N·cm -3 for the changing room and chemical workshop.